Motivations and incentives for mechanization in Zambia: a mixed-methods analysis - Mulungu, Kelvin; Ngoma, Lushomo Molly; Mhembere, Rumbidzai; Manyanga, Mark; Simutowe, Esau; Thierfelder, Christian; Matin, Md. Abdul; Ngoma, Hambulo (Taylor & Francis, 2025)
Smallholder farmers in Zambia face low agricultural productivity, and while tractor mechanization offers a solution, adoption rates remain low. The contextual factors driving this low uptake, including farmers’ preferences for different ownership and financing models, are not well understood. This study uses a mixed-methods approach, including surveys with 208 farmers, 18 focus group discussions (FGDs) and 28 key informant interviews (KIIs) across three districts in Zambia to examine these issues. The analysis shows that the motivations for tractor ownership are centred around both productivity enhancement and income generation through service provision, with farmers valuing tractors’ ability to improve operational timeliness given narrowing planting windows. The results reveal a clear divergence in ownership preferences. Individual ownership is favoured by male farmers and those in more mechanized districts seeking operational autonomy, while group ownership is preferred by female farmers and those in less-mechanized areas for its cost-sharing and risk-management benefits. In terms of incentives for ownership, risk-contingent credit (RCC), particularly when bundled with repair insurance, emerges as the most desirable incentive for encouraging tractor ownership. This highlights the need to de-risk mechanization investments. Key barriers to adoption include high maintenance costs, poor access to spare parts and the financial strains due to social obligations. These results demonstrate that a ‘one-size-fits-all’ approach to promoting mechanization is ineffective. Instead, successful interventions must be flexible, gender-responsive and tailored to the local context. Such an approach would likely increase ownership and improve livelihoods.